Charting cognitive and volumetric trajectories after stroke: protocol for the Cognition And Neocortical Volume After Stroke (CANVAS) study. Issue 6 (3rd June 2014) - Brodtmann, Amy; Werden, Emilio; Pardoe, Heath; Li, Qi; Jackson, Graeme; Donnan, Geoffrey; Cowie, Tiffany; Bradshaw, Jennifer; Darby, David; Cumming, Toby
<x xml:space="preserve">Abstract</x> Rationale Globally, stroke and dementia are leading causes of disability and mortality. More than one third of stroke patients will develop dementia, but mechanisms are unclear. Aims The study aims to establish whether brain volume change is associated with poststroke dementia, and to elucidate potential causal mechanisms, including genetic markers, amyloid deposition and vascular risk factors. An understanding of whether – and in whom – stroke is neurodegenerative is critical for the strategic use of potential disease‐modifying therapies. Hypotheses That stroke patients will exhibit greater brain volume loss than comparable cohorts of stroke‐free controls; and that those who develop dementia will exhibit greater brain volume loss than those who do not. Design Advanced brain imaging techniques are used to longitudinally measure brain volume and cortical thickness in 135 stroke patients. Concurrent neuropsychological testing will correlate clinical profile with these measures. Primary outcomes Primary imaging end‐point is brain volume change between three‐months and three‐years poststroke; primary clinical outcome is the presence of dementia at three‐years. Secondary outcomes We will examine the correlations with the following variables: dementia subtype; physical activity levels; behavioral dysfunction as measured by patient and caregiver‐reported scales; structural and functional brain connectivity disruption; apolipoprotein E; and specific neuropsychological test scores. Discussion Magnetic resonance imaging markers of structural brain aging and performance on neuropsychological tests are powerful predictors of dementia. We need to understand the trajectory of regional brain volume change and cognitive decline in patients after stroke. This will allow future risk stratification for prognostic counseling, service planning, and early therapeutic intervention.